2020
DOI: 10.1038/s41598-020-72733-w
|View full text |Cite
|
Sign up to set email alerts
|

Systematic experimental investigation of the obstacle effect during non-competitive and extremely competitive evacuations

Abstract: Although some experimental evidence showed that an obstacle placed in front of a door allows making people’s evacuations faster, the efficacy of such a solution has been debated for over 15 years. Researchers are split between those who found the obstacle beneficial and those who could not find a significant difference without it. One of the reasons for the several conclusions lies in the variety of the experiments performed so far, both in terms of competitiveness among participants, geometrical configuration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(30 citation statements)
references
References 40 publications
0
30
0
Order By: Relevance
“…The term “obstacle effect” describes the observation that under emergency evacuation conditions, the transportation at the bottleneck can be counterintuitively increased by a suitably placed obstacle near the exit. Many researchers have explored this topic using both simulation 15 , 16 and empirical 17 , 18 methods regarding, to name a few, the effect of obstacle size and position 19 , 20 , and the effect of corner exit rather than middle exit 21 , 22 . However, the obstacle and corner exit effects are applied to emergency escape conditions where the clogging results from the extremely small distance between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…The term “obstacle effect” describes the observation that under emergency evacuation conditions, the transportation at the bottleneck can be counterintuitively increased by a suitably placed obstacle near the exit. Many researchers have explored this topic using both simulation 15 , 16 and empirical 17 , 18 methods regarding, to name a few, the effect of obstacle size and position 19 , 20 , and the effect of corner exit rather than middle exit 21 , 22 . However, the obstacle and corner exit effects are applied to emergency escape conditions where the clogging results from the extremely small distance between individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Many scholars have studied the influence of obstacle by performing experimental and simulation research. Up to now, studies on the topic of exploring the effect of obstacle on pedestrian motion features mainly focus on the effects of obstacle size [1], position [2,3], shape [4,5], spatial layout [6][7][8] and type [9] on evacuation efficiency and path selection features [10]. It has been found that obstacles influence pedestrian movement characteristics and evacuation efficiency [11].…”
Section: Introductionmentioning
confidence: 99%
“…After this work, the increment of the flow rate by suitably placing an obstacle in front of the gate has been taken as a hallmark of pedestrian dynamics and, accordingly, it has been reproduced by most of the recently proposed models [2][3][4][5][6][7][8] . Nevertheless, a robust experimental demonstration of the obstacle effectiveness in pedestrian dynamics is still lacking given that the existing results are contradictory [9][10][11][12][13][14][15] . Paradoxically, this experimental evidence exists for other systems as i) the passage of animals such as sheep 16,17 or mice 18 through narrow doors, and ii) the discharge of granular matter from a silo [19][20][21][22] .…”
Section: Introductionmentioning
confidence: 99%